Serological prevalance of leptospiral infection in captive Malayan porcupiness (Hystrix brachyura) - Abdul Kadir, Siti Nurdiyana; Bahaman, Abdul Rani; Kumar Sharma, Reuben Sunil; Che' Amat, Azlan; Abdul Razak, Mohd Firdaus Ariff (Veterinary Association Malaysia, 2016)
Leptospirosis is recognised as one of the leading zoonotic diseases and rodents have been implicated as one of the natural reservoirs of the disease. The Malayan porcupines (Hystrix brachyura) which are also a rodent could possibly be a carrier of leptospiral organisms. This study was conducted to determine the serological prevalence of leptospiral infection among captive Malayan porcupines and to disclose the possibility of porcupines as a reservoir for leptospiral infection. Fifty serum samples were obtained from the Malayan porcupines kept in captivity at the Wildlife Conservation Centre, Sungai Dusun, Malaysia. The microscopic agglutination test (MAT) was performed on the serum samples to detect the presence of agglutinating antibodies to a panel of 16 Leptospira serovars (Australis, Autumnalis, Ballum, Bataviae, Canicola, Celledoni, Djasiman, Hardjobovis, Hardjopratjino, Hebdomadis, Hurstbridge, Icterohaemorrhagiae, Javanica, Pomona, Pyrogenes and Sejroe). From the serological test, 18% (n=9/50) of the Malayan porcupines tested had leptospiral antibodies to serovars Javanica (8%), Hurstbridge (4%), Ballum (2%), Celledoni (2%) and Hardjoprajitno (2%). It is seen that this study disclosed a high prevalence of leptospiral infection in the Malayan porcupines tested and indicated that the Malayan porcupines could possibly be a source of leptospirosis to other animals including humans and that they might play an important role in the epidemiology of leptospiral infection in the country.